2020
DOI: 10.1186/s13662-020-03116-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of delay strategy on transmission dynamics of HIV/AIDS disease

Abstract: In this manuscript, we investigate a nonlinear delayed model to study the dynamics of human-immunodeficiency-virus in the population. For analysis, we find the equilibria of a susceptible–infectious–immune system with a delay term. The well-established tools such as the Routh–Hurwitz criterion, Volterra–Lyapunov function, and Lasalle invariance principle are presented to investigate the stability of the model. The reproduction number and sensitivity of parameters are investigated. If the delay tactics are decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Radosavljevic et al suggested the curing techniques for the bioterrorist attack of anthrax [28]. Mathematical techniques were studied to analyze the transmission of infectious diseases [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In this paper, we study the dynamics of anthrax disease via computational methods.…”
Section: Introductionmentioning
confidence: 99%
“…Radosavljevic et al suggested the curing techniques for the bioterrorist attack of anthrax [28]. Mathematical techniques were studied to analyze the transmission of infectious diseases [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In this paper, we study the dynamics of anthrax disease via computational methods.…”
Section: Introductionmentioning
confidence: 99%
“…Their paper proposed one of the newest approaches to conditionbased maintenance modeling. There are also plenty of research papers on Machine learning [23], optimization [24][25][26][27][28][29][30] and mathematical modeling of different systems [31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Several biological phenomena and processes can be formulating in the language of mathematics in the framework of ordinary differential equations, fractional differential equations, impulsive differential equations, stochastic differential equations, delay differential equations, etc. [ 2 , 3 , 4 , 5 , 6 ]. Different assumptions, laws, axioms governing these processes are used in the formulation of these mathematical models to show the intricate dynamics of biological phenomena.…”
Section: Introductionmentioning
confidence: 99%